PENGARUHSTORE ATMOSPHERE DAN PROMOSI TERHADAP SHOPPING EMOTION DAN IMPULSE BUYING PADA SUPERMARKET HALIMAH LYTECH HOMEBATAM CENTRE” - Rahmat Hidayat; Risa Erika (Politeknik Negeri Bengkalis, 2017)
Abstract: Along with the increasing creativity of retail business people impact on the increasing frequency of competition for market share. With a variety of promotional strategies offered, it is expected that consumers who become the main target can be affected and make purchases Impulsive. This study aims to determine the effect of Store Atmosphere and Promotion on Impulse Buying through Shopping Emotion as an intervening variable on Supermarket con- sumers Halimah Lytech Home Batam Center. Data analysis technique used is path analysis, with sample of 100 respondens by using Accidental Sampling technique which is part of non-probability sampling. The results of this study explain that shopping emotion indirectly can affect the relationship between store atmosphere and promotion of impulse buying at Halimah Supermarket. These results illustrate that impulse buying will increase if shopping emotion has a greater influence. Keywords:Impulse Buying, Promotion, Shopping Emotion, Store Atmosphere